1985
DOI: 10.1159/000225998
|View full text |Cite
|
Sign up to set email alerts
|

Is Porphyria cutanea tarda a Risk Factor in the Development of Hepatocellular Carcinoma?

Abstract: A patient with alcoholic liver cirrhosis, diabetes mellitus and porphyria cutanea tarda (PCT) is described, who subsequently died of hepatocellular carcinoma. The literature relating PCT to the incidence of primary hepatoma is reviewed, and the mechanisms underlying this possible association are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Liver Patients with PCT are reported to be at risk for developing hepatocellular carcinoma (13,(40)(41)(42); conversely, some benign or malignant liver tumors can overproduce uroporphyrin and induce PCT (43)(44)(45).…”
Section: Porphyria Cutanea Tardamentioning
confidence: 99%
“…Liver Patients with PCT are reported to be at risk for developing hepatocellular carcinoma (13,(40)(41)(42); conversely, some benign or malignant liver tumors can overproduce uroporphyrin and induce PCT (43)(44)(45).…”
Section: Porphyria Cutanea Tardamentioning
confidence: 99%
“…Selected References Andant et al 1997;Bengtsson and Hardell 1986;Berman and Braun 1962;Bjersing et al 1996;Cassiman et al 2008;Deybach and Puy 2011;Lim and Mascaro 1995;Lithner and Wetterberg 1984;Salata et al 1985;Schneider-Yin et al 2010;and Stewart 2012. In patients with porphyria cutanea tarda, the pathogenesis of liver tumors is particularly complex, as this form of porphyria is associated with HCV and HBV infection, hemochromatosis/iron overload, and specifically alcoholic liver disease, known causes of HCC (Ryan Caballes et al 2012). Relatively few patients develop HCC in porphyria cutanea tarda, with a yearly incidence of less than 1 % per patient year of follow-up (Kordac 1972;Packe and Clarke 1985;Gisbert et al 2004;Whittle et al 2010), and risk factors for HCC were the presence of liver cirrhosis, male sex, and age over 51 (Salata et al 1985). Porphyria cutanea tarda can occur in combination with hereditary hemochromatosis, the condition being complicated with HCC (Mogl et al 2007).…”
Section: Porphyriasmentioning
confidence: 99%
“…Porphyry in patients with PLC as a paraneoplastic phenomenon is a well-documented but rare condition [19, 35, 36]. The reported cases had all photosensitive skin lesions, but in several instances the pattern of porphyrin excretion was not consistent with true PCT.…”
Section: Introductionmentioning
confidence: 98%
“…The most common type of PCT is an acquired form, which is triggered by toxic (e.g., alcohol) and infectious (e.g., hepatitis C virus) factors or haemosiderosis [28, 31, 32], and liver cirrhosis and hepatic iron overload are common associated findings [19]. Although each of these factors is known to increase the risk of HCC as well [5, 6, 33, 34], it has been suggested that PCT per se increases this risk further [18, 22].…”
Section: Introductionmentioning
confidence: 99%